Surface scaling resistance of concrete modified with bituminous addition - Kosior‐Kazberuk, Marta; Jezierski, Walery (Journal of Civil Engineering and Management, 2004)
Deterioration of concrete due to surface scaling is a very serious durability problem faced by the construction industry in cold environments. The experimental results of resistance to scaling due to cyclic freezing and thawing in the presence of 3% NaCl solution (de‐icing agent) of not air‐entrained concrete with and without bituminous addition are presented and discussed in the paper. The results have been analysed using the analysis of variance and regression to verify the effect of addition content, number of freeze‐thaw cycles and the sort of cement on concrete ability to scaling. The statistical analysis showed that the bituminous addition significantly improves the scaling resistance of Portland cement concrete.First Published Online: 14 Oct 2010